Literasi Digital dalam Pembelajaran Pendidikan Agama Kristen: Strategi Penguatan Spiritualitas dan Moralitas Nilai-nilai Kristen - Elisa Nimbo Sumual; Yohana Fajar Rahayu (STT Bala Keselamatan Palu, 2026)
The development of digital technology has significantly transformed the learning process in Christian Religious Education within modern digital culture. The use of social media and the boundless flow of information influence the spirituality, morality and character of learners in their daily lives. These circumstances require Christian Religious Education to integrate digital literacy based on Biblical values in a wise and responsible manner. This study aims to analyse digital literacy as a strategy for strengthening Christian spirituality and morality in Christian Religious Education. The research method employs a descriptive qualitative approach through a literature review of various scientific and theological sources. The results indicate that digital literacy helps students use technology critically, ethically, and reflectively in accordance with Christian teachings. The integration of digital media into learning also strengthens students’ Christian character, spiritual discipline, and moral awareness. Digital literacy has become an essential component of contemporary Christian Religious Education pedagogy. Strengthening spirituality and morality requires synergy between schools, families, and churches. This approach fosters a generation of Christians who are faithful, of good character, and responsible in the modern digital age. Abstrak: Perkembangan teknologi digital dan informatika membawa perubahan besar proses pembelajaran Pendidikan Agama Kristen di tengah budaya digital modern. Terlebih adanya penggunaan media sosial dan arus informasi tanpa batas sangat memengaruhi spiritualitas, moralitas, serta karakter peserta didik dalam kehidupan sehari-hari. Kondisi tersebut menuntut Pendidikan Agama Kristen mengintegrasikan literasi digital berbasis nilai alkitabiah secara bijaksana dan bertanggung jawab. Penelitian ini bertujuan menganalisis literasi digital sebagai strategi penguatan spiritualitas dan moralitas nilai-nilai Kristen dalam pembelajaran Pendidikan Agama Kristen. Metode penelitian menggunakan pendekatan kualitatif deskriptif melalui studi pustaka dari berbagai sumber ilmiah dan teologis. Hasil penelitian menunjukkan bahwa literasi digital membantu peserta didik menggunakan teknologi secara kritis, etis, dan reflektif sesuai ajaran Kristen. Integrasi media digital dalam pembelajaran juga memperkuat karakter Kristiani, disiplin rohani, dan kesadaran moral peserta didik. Literasi digital menjadi bagian penting dalam pedagogi Pendidikan Agama Kristen masa kini. Penguatan spiritualitas dan moralitas membutuhkan sinergi sekolah, keluarga, dan gereja.